Download Presentation
## WARM UP

- - - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - - -

**WARM UP**4 EVALUATING EXPRESSIONS Evaluate the expression for the given value of the variable (Lesson 2.5). -3(x) when x = 9 4(-6)(m) when m = -2 -5(-n)(-n) when n = 2 2(-1)(-x)3 when x = -3**WARM UP**3 EVALUATING EXPRESSIONS Evaluate the expression for the given value of the variable (Lesson 2.5). -3(x) when x = 9 4(-6)(m) when m = -2 -5(-n)(-n) when n = 2 2(-1)(-x)3 when x = -3**WARM UP**2 EVALUATING EXPRESSIONS Evaluate the expression for the given value of the variable (Lesson 2.5). -3(x) when x = 9 4(-6)(m) when m = -2 -5(-n)(-n) when n = 2 2(-1)(-x)3 when x = -3**WARM UP**1 EVALUATING EXPRESSIONS Evaluate the expression for the given value of the variable (Lesson 2.5). -3(x) when x = 9 4(-6)(m) when m = -2 -5(-n)(-n) when n = 2 2(-1)(-x)3 when x = -3**WARM UP**0 EVALUATING EXPRESSIONS Evaluate the expression for the given value of the variable (Lesson 2.5). -3(x) when x = 9 4(-6)(m) when m = -2 -5(-n)(-n) when n = 2 2(-1)(-x)3 when x = -3**9.6 Solving Quadratic Equations by the Quadratic Formula**GOAL Use the quadratic formula to solve a quadratic equation. KEY WORDS Quadratic formula Vertical Motion model**9.6 Solving Quadratic Equations by the Quadratic Formula**The quadratic formula gives the solutions of ax2 + bx + c = 0 in terms of the coefficients a, b and c.**9.6 Solving Quadratic Equations by the Quadratic Formula**The solutions of the quadratic equation ax2 + bx + c = 0 are: x = when a ≠ 0 and b2 – 4ac > 0. THE QUADRATIC FORMULA**EXAMPLE 1 Use the Quadratic Formala**Solve x2+ 9x + 14 = 0 SOLUTION x2 + 9x + 14 = 0 Identify a =1, b = 9 and c = 14 x = Substitute values in the quadratic formula. x = Simplify x = Solutions. ANSWER> The two solutions are x = -2 and -7. 9.6 Solving Quadratic Equations by the Quadratic Formula**9.6 Solving Quadratic Equations by the Quadratic Formula**Checkpoint Use the Quadratic Formula. Use the quadratic formula to solve the equation. x2 – 4x + 3 = 0 2x2 + x - 10 = 0 -x2 + 3x + 4 = 0